Genealogy and knowledge in Muslim societies : understanding the past - Savant, Sarah Bowen; Felipe, Helena de (Exploring Muslim contexts., 2014)
Published in Association with the Institute for the Study of Muslim Civilisations. Explores the generation, preservation and manipulation of genealogical knowledge. From the Prophet's family tree to the present, ideas about kinship and descent have shaped communal and national identities in Muslim societies. So an understanding of genealogy is therefore vital to our understanding of Muslim societies, particularly with regard to the generation, preservation and manipulation of genealogical knowledge. These 9 case studies link genealogical knowledge to particular circumstances in which it was created, circulated and promoted. They stress the malleability of kinship and memory, and the interests this malleability serves. Key Features. Draws on primary sources from across the Middle East, the Maghreb, and Sub-Saharan Africa, ranging from works of the classical Arabic heritage to oral testimonies gained from fieldwork Questions how genealogical knowledge has been generated, how it has empowered political and religious elites and how it has shaped understandings about the past - including those of modern scholars Examines the authenticity, legitimacy and institutionalisation of genealogical knowledge Looks at the bases for sectarian, tribal, ethnic and other identities Explores hierarchy and grounds for prestige and infamy